2022 IEEE 25th International Conference on Intelligent Transportation Systems (ITSC) 2022
DOI: 10.1109/itsc55140.2022.9922419
|View full text |Cite
|
Sign up to set email alerts
|

A Multidimensional Graph Fourier Transformation Neural Network for Vehicle Trajectory Prediction

Abstract: This work provides a comprehensive derivation of the parameter gradients for GATv2 [4], a widely used implementation of Graph Attention Networks (GATs). GATs have proven to be powerful frameworks for processing graph-structured data and, hence, have been used in a range of applications. However, the achieved performance by these attempts has been found to be inconsistent across different datasets and the reasons for this remains an open research question. As the gradient flow provides valuable insights into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Overall, we find that deep learning models can benefit from representational fusion for classification tasks such as clinical toxicity, however, the guidelines for when and how representational fusion is beneficial remains an open question. Recent investigations have found that GNNs can be unstable when training on classifications tasks [ 39 – 43 ]. For example, GCNs have been reportedly unstable when the number of node features becomes too large [ 42 ] and GATv2 suffers from initialization instabilities [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, we find that deep learning models can benefit from representational fusion for classification tasks such as clinical toxicity, however, the guidelines for when and how representational fusion is beneficial remains an open question. Recent investigations have found that GNNs can be unstable when training on classifications tasks [ 39 – 43 ]. For example, GCNs have been reportedly unstable when the number of node features becomes too large [ 42 ] and GATv2 suffers from initialization instabilities [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recent investigations have found that GNNs can be unstable when training on classifications tasks [ 39 – 43 ]. For example, GCNs have been reportedly unstable when the number of node features becomes too large [ 42 ] and GATv2 suffers from initialization instabilities [ 43 ]. These fundamental limitations of the GNNs may explain the more variable performance on classification tasks.…”
Section: Resultsmentioning
confidence: 99%
“…To gain understanding of the training behavior of GATv2 [4], this work derives the gradients for its network parameters. This study is an addition to [2], in which potential drawbacks and issues of GATv2 are analyzed. Certain hypotheses of [2] are evidenced and supported upon the outcome of this study.…”
Section: Introductionmentioning
confidence: 99%
“…This study is an addition to [2], in which potential drawbacks and issues of GATv2 are analyzed. Certain hypotheses of [2] are evidenced and supported upon the outcome of this study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation